Displacemon electromechanics: How to detect quantum interference in a nanomechanical resonator - Khosla, K; Vanner, M; Ares, N; Laird, E (American Physical Society, 2018)
We introduce the "displacemon" electromechanical architecture that comprises a vibrating nanobeam, e.g., a carbon nanotube, flux coupled to a superconducting qubit. This platform can achieve strong and even ultrastrong coupling, enabling a variety of quantum protocols. We use this system to describe a protocol for generating and measuring quantum interference between trajectories of a nanomechanical resonator. The scheme uses a sequence of qubit manipulations and measurements to cool the resonator, to apply two effective diffraction gratings, and then to measure the resulting interference pattern. We demonstrate the feasibility of generating a spatially distinct quantum superposition state of motion containing more than 106 nucleons using a vibrating nanotube acting as a junction in this new superconducting qubit configuration.